Influence of Allium sativum on Pharmacodynamics and Pharmacokinetics of Gliclazide in Normal Rabbits - Aminabee, Shaik (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: In this chapter, the influence of selected dose of Allium sativum (84 mg/1.5 kg bd.wt) on the pharmacodynamics and pharmacokinetics of selected dose of gliclazide (5.6 mg/1.5 kg bd.wt) was studied in normal rabbits. Materials and Methods: Materials required were purchased from Sai Chemicals, Visakhapatnam, India. Inbred adult Wistar rabbits of either sex were used for the study. Gliclazide (TD) was administered orally to all the rabbits. After a wash out period of 1 week, the same groups of animals were administered with Allium sativum (84 mg/1.5 kg bd.wt.) orally. Again after a further washout period of 1 week, the same group was administered with A. sativum (84 mg/1.5 kg bd.wt.) orally, 30 min before the administration of gliclazide (5.6 mg/1.5 kg bd.wt). Blood samples were withdrawn at 0, 1, 2, 3, 4, 6, 8, 12, 16, 20, and 24 h intervals from marginal ear vein puncture and were analyzed for blood glucose by GOD/POD method in all the experiments and serum gliclazide. Results: A. sativum has found to enhance the hypoglycemic effect of gliclazide. There was a considerable percent blood glucose reduction with gliclazide (5.6 mg/1.5 kg bd.wt) before and after treatment with Allium sativum (104 mg/kg) in rabbits.Conclusion: The interaction between A. sativum and gliclazide appears to be pharmacodynamic and pharmacokinetic in nature.